Identification The Bioactive Components Of Brown Seaweed (Sargassum plagyophyllum)Extracted WithMethanol - Indah Azisari; Nur Ira Sari; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTSeaweed is one of the many biological resources found in Indonesian coastal sea containing nutrients and potential bioactive compounds for human health. This study was aimed  to determine the bioactive compound  of S. plagyophyllum extracted with methanol qualitatively. The research method used is an experiment by conducting a series of brown seaweed extraction experiments with methanol as a solvent. Parameter analysis of the identification of bioactive compounds  qualitatively. The results showed that the bioactive components found in brown seaweed (S. plagyophyllum) extracted with methanol consisted of flavonoids, steroids/terpenoids, saponins and phenolics.Kata kunci:extracted;bioactive component; methanol;S. plagyophyllum